The sum of the series $\displaystyle 1+\frac{\sqrt{2}-1}{2\sqrt{2}}+\frac{3-2\sqrt{2}}{12}+\frac{5\sqrt{2}-7}{24\sqrt{2}}+\frac{17-12\sqrt{2}}{80}+.....\infty$

$\bf{My\; Try::}$Here $3-2\sqrt{2} = (\sqrt{2}-1)^2$ and $5\sqrt{2}-7 = (\sqrt{2}-1)^3$

similaryly $17-12\sqrt{2} = (\sqrt{2}-1)^4\;,$ Now let $(\sqrt{2}-1)=x>0$

So our series convert into $$1+\frac{x^2}{2\sqrt{2}}+\frac{x^4}{12}+\frac{x^6}{24\sqrt{2}}+\frac{x^8}{80}+........$$

Now how can i solve after that, Help required, Thanks

  • 2
    $\begingroup$ Try to put $y = \frac{x}{\sqrt{2}}$ to simplify it further to $\sum \frac{y^n}{a_n}$ where $a_n$ are integers. Then try to find a pattern in this integer list: $a_n = 2,6,12,20$ for $n=1,2,3,4$ $\endgroup$ – Winther Jun 9 '16 at 3:26
  • 1
    $\begingroup$ What exactly is the formula for the $n$th term of the series? $\endgroup$ – DanielWainfleet Jun 9 '16 at 4:12

From the suggestion by @Winther, express the series as

$$S = 1+\sum_{n=1}^{\infty} a_n x^n $$

where $a_n = \frac1{n (n+1)}$ and $x=1-\frac1{\sqrt{2}} $. Then

$$\begin{align}S &= 1+\sum_{n=1}^{\infty} \frac{x^n}{n} - \sum_{n=1}^{\infty} \frac{x^n}{n+1}\\ &= 1-\log{(1-x)} - \frac1x\left (-\log{(1-x)}-x \right )\\ &= 2-\left (1-\frac1x \right ) \log{(1-x)}\end{align}$$


$$1-\frac1x = 1-\frac{\sqrt{2}}{\sqrt{2}-1} = -\frac1{\sqrt{2}-1}$$


$$S=2 - \frac12 (\sqrt{2}+1) \log{2} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.